The Sounds of Horseshoe a Zoopoetic Reading of Yılkı Atı by Abbas Sayar - Özlem Akyol (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
The new perception influenced by the cultural and linguistic turns of the late 20th century requires a less anthropocentric vision for the 21st century. By extension, an increasing scholarly interest in the relation between humans and nonhuman animals and the agentive role of the latter result in the emergence of “zoopoetics.” The theory includes literature to explore different nonhuman agentive forms by analysing how literary texts reproduce animals’ modes of being and reveals that poetic creation is not only sustained through human affair but animals also take an active part in making and shaping poetry. As Aaron Moe indicates “[N]onhuman animals (zoion) are makers (poiesis), and they have agency in that making” (2013, p. 2). A zoopoetic reading of literary texts which focuses on the nonhumans’ creative modes not only shows how nonhuman animals function in conducting the lives of other characters and the very substance of narrative but also forms a basis for the manifestation of the ethical and social dimension of such texts. In this sense, Abbas Sayar, in Yılkı Atı (1970) positions a horse in the centre of the narrative by making it truly an agentive form in a way that the horse’s attitude affects other characters’ lives and the overall formation of the text and, more importantly, makes the reader ponder about the proximity between humans and nonhuman animals as well as socioeconomic issues of 1970s’ Central Anatolia. In this article, then, Yılkı Atı will be explored under the light of zoopoetic theories.